Development of Discovery Learning-Based E-Module with Video Demonstration to Improve Students’ Conceptual Understanding on Reaction Rate and Chemical Equilibrium - Hardeli; Sakinah Alora, Bundani; Mulyani, Sri; permatasari, Putri (Phenomenon : Jurnal Pendidikan MIPA, 2024)
Learning chemistry concepts such as reaction rate and chemical equilibrium often pose challenges for students due to their abstract nature and limited opportunities for laboratory practice. This research aims to determine the validity, practicality, and effectiveness of the discovery learning-based emodule with a video demonstration on high school students' reaction rate and chemical equilibrium subjects. The type of research carried out was education design research (EDR) with the Plomp development model. This research involved six chemistry lecturers of the Faculty of Mathematics and Natural Sciences and Faculty of Engineering Universitas Negeri Padang. Teachers and students at the high school level from several schools were also involved in this research. Questionnaires, observations, interviews, and post-test and pretest scores were used to retrieve data. Based on the results, it was known that the two e-modules were in the valid category with values of 0.866 and 0.892. Furthermore, both e-modules have practicality values of 0.85 and 0.84 from teachers, respectively, and 0.96 and 0.87 from students, putting them in the practical category. The effectiveness values of the two e-modules were 0.59 and 0.67, so they were categorized as quite effective. The effectiveness of the developed e-module was evaluated based on the improvement of students’ conceptual understanding in the cognitive domain.